Substantiation of allocation of protected territories in Tomsk; Korus 2005; Vol. 1 - Krotova Y. V. (2005, 2005)
One of the ways of the city environment's improvement is its gardening. Recreational zones serve for short-term or long rest of people, removal of weariness from industrial pressure, exhaustion from city noise and other negative influences of settlements.